Calculus (3rd Edition)

Published by W. H. Freeman
ISBN 10: 1464125260
ISBN 13: 978-1-46412-526-3

Chapter 11 - Infinite Series - 11.1 Sequences - Exercises - Page 537: 30



Work Step by Step

Using Theorem 1, we have $$ \lim\limits_{n \to \infty}{e^{-n}}=0.$$ Now, since $e^{-x}$ is continuous, then by Theorem 4, we have $$\lim_{n\to \infty}\tan^{-1}{e^{-n}}= \tan^{-1}{ \lim_{n\to \infty}e^{-n}}=\tan^{-1}0=0.$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.